Design, synthesis, and biological evaluation of novel azaspirooxindolinone derivatives as potent inhibitors of ITK and BTK-dependent cancers - Mudasani, Gopal; Rampeesa, Naveen Kumar; Anugu, Sreenivasa Reddy; Muddasani, Pullareddy; Gurská, Soňa; Džubák, Petr; Hajdúch, Marián; Das, Viswanath; Gundla, Rambabu (Bioorganic & medicinal chemistry, 2025)
Interleukin-2-inducible T-cell kinase (ITK) and Bruton's tyrosine kinase (BTK) are two important members of the Tec family with crucial roles in immune system function. Deregulation in ITK and BTK activity is linked to several hematological malignancies, making them key targets for cancer immunotherapy. In this study, we synthesized a series of azaspirooxindolinone derivatives and evaluated their cytotoxic activity against ITK/BTK-negative and positive cancer cell lines, followed by enzymatic inhibition studies to assess the ITK/BTK kinase selectivity of two hit compounds. Several compounds demonstrated selective cytotoxicity against ITK- or BTK-expressing cells. Compound 3d exhibited high cytotoxicity in ITK-positive Jurkat (IC50 = 3.58 μM) and BTK-positive Ramos (IC50 = 3.06 μM) cells, while compound 3j showed strong cytotoxicity in Ramos (IC50 = 1.38 μM) and Jurkat (IC50 = 4.16 μM) cells. Compounds 3a and 3e were selectively cytotoxic in Jurkat cells (IC50 = 9.36 μM and 10.85 μM, respectively), while compounds 3f and 3g were highly cytotoxic in Ramos cells (IC50 = 1.82 μM and 1.42 μM, respectively). None of the active compounds exhibited cytotoxicity in non-cancer cell lines (IC50 > 50 μM), demonstrating their selectivity for malignant cells. Enzyme inhibition assay showed that 3d is a selective ITK inhibitor (IC50 = 0.91 μM) with no detectable BTK inhibition, aligning with its strong activity in ITK-positive cells. In contrast, compound 3j did not inhibit ITK or BTK enzymatically, suggesting an alternative mechanism of action. These findings highlight 3d as a promising ITK inhibitor and warrant further investigation to elucidate its mechanism of action.
Keywords: proteinkinasa BTK; Drug Screening Assays, Antitumor; Humans; inhibitory proteinkinas; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Oxindoles; Molecular Docking Simulation; spirosloučeniny; Antineoplastic Agents; lidé; tyrosinkinasy; proliferace buněk; molekulární struktura; Drug Design; Molecular Structure; Protein Kinase Inhibitors; Protein-Tyrosine Kinases; Cell Proliferation; racionální návrh léčiv; oxindoly; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; vztah mezi dávkou a účinkem léčiva; Cell Line, Tumor; Agammaglobulinaemia Tyrosine Kinase; Spiro Compounds